ANALISIS PENGGUNAAN BAHASA DALAM SLOGAN POLITIK DAN KANDUNGAN PENDIDIKAN KARAKTER - Adhani, Agnes; Meilasari, Priska (Widya Warta, 2021)
The aims of this research are to know the language varieties that are used, to describe the sentence construction, to reveal the communicative act, and to expose the contended charactereducation in political slogans. This is a descriptive qualitative research on 37 political slogans retrieved from news, political portal, or political partyâ€™s website on internet. From this research, it is shown that (1) the language varieties that are used in political slogan: 28 data of Indonesian langauge, 7 data of slang expressions, 1 datum of Javanesse language, and 1 data of English language, (2) the sentence constructions that are applied are 20 data of exclamative sentences, 11 data of declarative sentences, 5 data of imperative sentences, and 1 datum of interogative sentence, (3) communicative acts that are shown in 37 data is clasiffied into asserting (20 data), suggesting (11 data), and inviting (6 data), (4)Â  there are 7 educational values found in political slogans, they are (a) 11 data of caring values, (b) 8 data of creative values, (c) 6 data of tough values, (d) 4 data of nasionalism values, (e) 3 data of politeness and communicativeness value, (f) 3 data of religious values, and (g) 2 data of honesty values.